Infection prevention in endoscopy practice: comparative evaluation of re-usable vs single-use endoscopic valves - L. Pasquale; A. Maurano; G. Cengia; P. Da Massa Carrara; B. Germanà; M.G. Graziani; G. Manes; A. Pisani; M. Golia; E. Marciano; L. Rodella; L. Schiffino; et al. (Elsevier, 2021)
Summary: Re-usable air/water and suction valves used in endoscopes often demonstrate risk of infection. To the authors' knowledge, the safety and efficacy of re-usable and single-use valves have not been compared to date. As such, a laboratory investigation was undertaken to compare the safety and efficacy of re-usable and single-use valves at 11 Italian endoscopy sites. Safety was evaluated by analysing the rinse liquid of reprocessed re-usable valves ready for use, and efficacy was assessed based on the completion of endoscopic procedures without valve malfunction. This study found significantly lower contamination of single-use valves compared with re-usable valves (0 vs 29.1%, respectively; P=0.007) and similar efficacy (97.6 vs 98.8%, respectively; P=ns). Microbiological analysis of the rinse liquid of reprocessed re-usable valves identified various surviving micro-organisms and highlighted their potential pathogenicity. Such data suggest that sterile single-use valves may be safer than re-usable valves, and have comparable performance.